MARINE MAGNETIC ANOMALIES: EVIDENCE THAT 'TINY WIGGLES' REPRESENT SHORT-PERIOD GEOMAGNETIC POLARITY INTERVALS - Roberts A.P.; Lewin-Harris J.C. (My University, 2000)
Since the 1960's, the geomagnetic polarity time scale, which is based on marine magnetic anomalies, has become fundamentally important in geochronology. Despite the importance of marine magnetic anomaly records, there has been longstanding uncertainty about the meaning of the smallest anomalies observed in these records. Small amplitude, short wavelength anomalies are frequently observed in marine magnetic anomaly records across fast-spreading oceanic crust (>50 mm/yr). The origin of these small-scale anomalies (referred to as 'tiny wiggles') has remained controversial over the last 30 years. 'Tiny wiggles' have been interpreted to represent either short-period polarity intervals or large-scale fluctuations in the ancient field intensity. We present palaeomagnetic evidence from a sedimentary record from the North Pacific Ocean, which demonstrates that two short, but clearly resolvable, polarity zones, in addition to a probable geomagnetic excursion, occur within Chron C5n.2n (9.92-10.95 Ma) where three 'tiny wiggles' have been reported on marine magnetic anomaly profiles. Relative palaeointensity data indicate that the field collapsed prior to and during the reversals (and during the excursion) but that it recovered to higher field intensities within the polarity intervals before collapsing to low values at the succeeding polarity transition. This indicates that some 'tiny wiggles' represent real short-period geomagnetic polarity intervals, while others may represent geomagnetic excursions. The existence of such short polarity intervals confirms the predictions of statistical analyses of geomagnetic reversal frequency and indicates that 'tiny wiggles' represent the maximum resolution of geomagnetic polarity intervals in marine magnetic anomaly records.
Keywords: MAGNETIC ANOMALIES; SECULAR VARIATIONS; REVERSALS; PALEOMAGNETISM